An Assessment of the Present and Future Labor Market in the Kurdistan Region-Iraq Implications for Policies to Increase Private-Sector Employment - Shatz, Howard J. (RAND Corporation, 2014)
The study addresses the question of how the Kurdistan Regional Government can improve the private-sector labor market in the Kurdistan Region-Iraq. Doing so will involve creating mechanisms by which job-seekers can develop the right skills and find employers who will hire them, employers can find the employees they need, and the government can create an enabling environment in which the best matches between job-seekers and employers can be made.